ANALISIS KORELASI KARAKTER AGRONOMI JAGUNG CALON HIBRIDA TERHADAP CEKAMAN NITROGEN RENDAH - Hasrun, Nurul Auliarahmah; Haris, Abdul; Efendi, Roy (Percetakan Umi Toaha Makassar, 2025)
Correlation analysis is a statistical method used to determine the level of relationship between traits in a plant. This study aimed to determine the correlation between agronomic traits that directly and indirectly affect the productivity of several hybrid corn genotypes under normal conditions and under low nitrogen stress. This research was conducted at the Food Crops Research and Assessment Installation (IP2TP) Bajeng, Gowa Regency, South Sulawesi Province, from July to October 2024. This study was conducted using a randomized split-plot design. The main plot was the fertilizer rate consisting of two levels: 200 kg N/ha (nn) and 100 kg N/ha (nr), while hybrid corn served as a subplot consisting of 25 genotypes and two control varieties (BISI 18 and ADV 777). The results showed that under normal nitrogen conditions, plant height, stem diameter, leaf area, soil plant analysis development, ear height, harvested ear weight, ear length, and weight per 1,000 kernels correlated significantly with productivity. Under low nitrogen stress, harvested ear weight and grain yield significantly influenced productivity, while anthesis silking interval correlated significantly at the 5% level (p<0.05).